Uji Daya Simpan Biskuit Dari Formulasi Campuran Tepung Labu Siam (Sechium Edule) dan Kacang Hijau (Vigna Radiata) - Mulyati Mulyati; Jamaludin Sakung (Universitas Tadulako, 2023)
The study aims to determine the shelf life of biscuits from a mixture of chayote flour (Sechium edule) and mung bean (Vigna radiata) flour. The samples used in this study were biscuits made from chayote flour (Sechium edule) and Mung beans (Vignaradiata). This research was carried out in June-September 2020 which began with the manufacture of biscuits from the formulation of chayote flour and Mung beans. Data analysis for estimating the shelf life of biscuits using the Arrhenius method. The results of the research using the ASLT method. Based on the results obtained, the shelf life of biscuits from a mixture of chayote flour (Sechium edule) and Mung bean (Vignaradiata) formulation was the highest, obtained by 100% chayote flour at 25 oC for 177 days. The highest 100% Mung beans were obtained at 25 oC for 176 days. The highest 50% chayote flour and 50% Mung beans were obtained at 25 oC for 187 days. The highest 75% chayote flour and 25% Mung beans were obtained at 25 oC for 170 days. The highest 25% chayote flour and 75% mung bean were obtained at 45oC for 195 days